Mechanism of Immune System Based Multipath Fault Tolerant Routing Algorithm for Wireless Sensor Networks. (11th December 2013) - Li, Hongbing; Xiong, Qingyu; Shi, Weiren; Chen, Liwan; Shi, Xin; Chen, Qiang
Abstract : It is significant to improve fault tolerance and transmission reliability for improving the overall performance of wireless sensor networks. Related studies on this issue become the hotspot at present. For issues that nodes fault or link quality can affect the transmission stability and reliability of the network, mechanism of immune system based multipath fault tolerant routing algorithm is presented for wireless sensor networks. Firstly, mechanism of immune system is adopted to establish the hierarchical clustering topology with superior performance of clustering compactness. Then nodes' comprehensive measurement (CM) values are calculated and the contour lines are established among cluster heads according to nodes gradient. Mechanism of immune system is applied to do the variation on the initial antibody population, namely, the multiple disjoint paths, to establish the final optimal transmission paths. Mathematical model is established to do the theoretical analysis on the performance of the algorithm. Through the simulation on the packet receiving rate, accuracy rate, and energy efficiency, the algorithm improves the transmission reliability, energy efficiency of the network, and shows superior performance of fault tolerance.